Unlocking Green Initiatives: A Comprehensive Study on Factors Influencing Employee Environmental Behavior at PT Petrokimia Gresik - Harmianto Purbawinasta, Liliek; Premananto, Gancar Candra (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2023)
Growing concerns about the company's environmental impact and the subsequent efforts to intervene with employees have proven ineffective at PT. Petrokimia Gresik. The lack of active participation among employees serves as evidence of the company's inability to foster environmentally conscious behavior. This research aims to assess the impact of company policies related to community social responsibility (CSR), the work environment's influence on employee well-being, individual employees' environmental knowledge, and leadership's role in ethical leadership on the development of environmental behavior among PT. Petrokimia Gresik employees. Employing qualitative methods and utilizing partial least square (PLS) for data analysis, this study reveals that corporate social responsibility programs, environmental knowledge, and employee well-being directly influence employees' environmental behavior. Additionally, the results indicate that employee well-being is shaped by environmental knowledge and ethical leadership. Through indirect testing, the study identifies employee well-being as a mediating variable between environmental knowledge and ethical leadership, influencing employees' environmental behavior. The dominant direct relationship of employee environmental knowledge in shaping green behavior, along with its indirect influence through the employee welfare variable, underscores the significance of fostering employee initiatives. Therefore, enhancing employee awareness at PT. Petrokimia Gresik necessitates an increase in environmental knowledge among employees to promote environmental conservation. Keyword: Employee green behaviour, PT. Petrokimia Gresik, employee well-being Peningkatan kepedulian terhadap dampak perusahaan terhadap lingkungan yang meningkatkan beragam upaya intervensi terhadap karyawan tidak berjalan efektif di PT. Petrokimia Gresik. Tingkat partisipasi karyawan yang rendah menjadi bukti dari ketidak efektivan perusahaan dalam membangun perilaku hijau karyawan. Penelitian ini bertujuan untuk mengetahui pengaruh kebijakan perusahaan melalui community social responsibility (CSR), lingkungan kerja melalui employee well-being, personal karyawan melalui environmental knowledge, dan pimpinan yang ditinjau dari ethical leadership terhadap employee green behaviour di PT. Petrokimia Gresik. Penelitian menggunakan metode kualitatif dengan partial least square (PLS) sebagai teknik analisis data. Penelitian ini menemukan bahwa program tanggung jawab sosial perusahaan, pengetahuan tentang lingkungan, dan kesejahteraan karyawan memiliki pengaruh langsung terhadap tindakan hijau karyawan. Hasil penelitian juga menunjukkan bahwa kesejahteraan karyawan dipengaruhi oleh pengetauan terhadap lingkungan dan kepemimpinan etik. Dalam proses pengujian secara tidak langsung, penelitian ini menemukan kesejahteraan karyawan menjadi variabel yang memediasi pengetahuan tentang lingkungan dan kepemimpinan etik terhadap tindakan hijau karyawan. Hubungan dominan secara langusng pengetahuan lingkungan karyawan terhadap pembentukan perilaku hijau yang juga berpengaruh secara tidak langsung melalui variabel kesejahteraan karyawan menunjukkan pembentukan inisiatif karyawan menjadi elemen penting, sehingga untuk meningkatkan kepedulian karyawan PT. Petrokimia Gresik dibutuhkan peningkatan pengetahuan karyawan tentang konservasi lingkungan. Kata Kunci: Tindakan Hijau Karyawan, PT. Petrokimia Gresik, Kesejahteraan Karyawan